Systematics and distribution of freshwater Audouinella (Arochaetiaceae, Rhodophyta) in Brazil - Necchi Júnior, O.; Zucchi, M. R. (Cambridge University Press, 1995)
Forty-five Brazilian populations of freshwater Audouinella were analysed using multivariate morphometrics. These populations were statistically related to seven type specimens. Five species are recognised on the basis of qualitative (plant colour and size, basal system type and branch angle) and quantitative (length and diameter of vegetative cells and monosporangia) characters. A. hermannii (syn. A. violacea) is characterised by a reddish colour, an irregular prostrate basal system, open branch angles (greater than or equal to 25 degrees) and small monosporangia (less than or equal to 15 mu m in diameter). A. macrospora (syn. A. chalybea var. brasiliensis) is distinguished from the other Brazilian species by having a bluish colour, a basal system composed of well-developed rhizoids, narrow branch angles (< 25 degrees) and large monosporangia (greater than or equal to 15 mu m in diameter). A. meiospora is microscopic and has a reddish colour, a basal system composed of creeping filaments, narrow branch angles and small monosporangia. A. pysmaea (syn. A. leibleinii) is characterised by being bluish, having an irregular prostrate basal system, narrow branch angles and small monosporangia. A, tenella is distinct from the other species by having a reddish colour, an irregular prostrate basal system, open branch angles, small monosporangia and small vegetative cells (less than or equal to 6 mu m in diameter). An identification key and revised descriptions and synonyms are presented for the five species. A. meiospora and A. tenella are reported for the first time for Brazil. A. macrospora and A. pygmaea were the most widespread species and occurred in tropical and subtropical regions. A. meiospora was found at two sites in a tropical rainforest region, whereas A. hermannii and A. tenella were found at only one site. Selected physical and chemical environmental data (temperature, specific conductance, current velocity, turbidity, pH and dissolved oxygen) are presented for most species.
Keywords: Acrochaetiaceae; Aadouinella; Brasil; Distribution; Rhodophyta; Stream